1967
DOI: 10.1107/s0365110x67001732
|View full text |Cite
|
Sign up to set email alerts
|

The conformation of non-aromatic ring compounds. XXVIII. The crystal structure of α-chloro-δ-valerolactam

Abstract: Crystals of ~-chloro-~-valerolactam are monoclinic with space group P2~/e and Z= 4. The lattice constants at room temperature are a=11.73, b=6-20, c=9.51 A., ,8=112-0 °. The structure was solved from a minimum function M4 which was directly computed and contoured at the machine output. Both b-and c-axis data were refined separately with a least-squares program and the results are compared. The molecule has a half-chair conformation with the chlorine atom in equatorial position. The peptide linkage NH-CO has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The amide bond in lactam ( 5) is also shorter than the amide bond in the pyrazolidinone (2a), 1.36 A, as well as that reported for a-chloro-6valerolactam, 1.37 A. 24 The carbonyl stretching frequency for lactam (3, 1 755 cm-', is anomalously high compared to that for the N-aryl compound,22 1735 cm-', while that for the N-aroyl-la~tarn,~~ 1 780 cm-', suggests that the lone pair on the nitrogen atom interacts with two different carbonyl groups. Carbonyl stretching frequencies for monocyclic plactams variously substituted on the carbon and nitrogen atoms of the ring have been reported 14ap25 in the range 1 685-1 785 cm-'.…”
supporting
confidence: 70%
“…The amide bond in lactam ( 5) is also shorter than the amide bond in the pyrazolidinone (2a), 1.36 A, as well as that reported for a-chloro-6valerolactam, 1.37 A. 24 The carbonyl stretching frequency for lactam (3, 1 755 cm-', is anomalously high compared to that for the N-aryl compound,22 1735 cm-', while that for the N-aroyl-la~tarn,~~ 1 780 cm-', suggests that the lone pair on the nitrogen atom interacts with two different carbonyl groups. Carbonyl stretching frequencies for monocyclic plactams variously substituted on the carbon and nitrogen atoms of the ring have been reported 14ap25 in the range 1 685-1 785 cm-'.…”
supporting
confidence: 70%
“…The obtained ring geometry of the succinimide fragment of (III') agrees well with the crystal data of 3-phenylpyrrolidine-2,5-dione (Argay and K~tlm/m 1973). The most closely related compound is 6-valerolactam and the crystal data of its ct-chloro derivative are available (Romers et al 1967). This reflects the overall tendency of MNDO and PM 3 to overestimate the length of the C-N bond in the amido groups (Stewart b, 1990.…”
Section: Resultsmentioning
confidence: 83%
“…The results suggested that ␦-valerolactam had the distinct deviations from planarity in the vicinity of the nitrogen atom, for the calculated value of the C-N-C(AO)-C torsional angle of ␦-valerolactam (Ϫ25.0°) differs markedly from its value in the chloro derivative (Ϫ8.8°) (6). The molecular conformation of the complex containing ␦-valerolactam is of interest to be used as a model to explain the conformational properties of proteins.…”
Section: Introductionmentioning
confidence: 70%